Preparation method and application of quantum dot film
By using organic phosphoric acid and polymer to modify quantum dots in the preparation of quantum dot films and using simple coating and annealing processes, the problems of high production cost and unstable quality in the prior art are solved, and large-area high-energy numbers are achieved The preparation of dot films is suitable for a variety of application fields.
Patent Information
- Application Number
- CN202411593419.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-18
AI Technical Summary
The prior art has problems such as high cost, uneven thickness, unstable film quality, and complex process when preparing quantum dot films, making it difficult to be suitable for large-scale industrial production and large-area film preparation.
The precursor solution is prepared by dissolving the quantum dot precursor components and organic phosphoric acid in an organic solvent, and then adding polymers is added, mixing them evenly to form a film solution. Finally, it is coated on the substrate material and annealed to obtain an organic Phosphoric acid and polymer modified quantum dot films.
It has achieved the preparation of a large-area high-energy sub-dot film, with low roughness, low defect density, uniform thickness, bright and uniform luminous, and is suitable for display, lighting, lasers, photodetectors and other fields.
Smart Images

Figure CN119463870A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of optoelectronic material devices, and specifically relates to a preparation method of a large-area high-performance quantum dot film and its application, which can be applied to new display, white light illumination, photoelectric detectors, lasers and other fields. Background Art
[0002] Quantum dots (QDs) are nanomaterials that can bind conduction band electrons, valence band holes, and excitons in three spatial dimensions. Compared with traditional luminescent materials such as rare earth phosphors and organic fluorescent molecules, quantum dots have significant advantages: (1) a wide color gamut can be achieved by adjusting the band gap by adjusting the size and composition; (2) ultra-high photoluminescence quantum yield; (3) high color accuracy based on a narrow emission spectrum; (4) low cost and scalable synthesis process; (5) small light scattering effect in the visible light region; (6) compatible with traditional device manufacturing processes, etc. These advantages make quantum dots stand out from many luminescent materials and have great application potential in lighting devices, new displays, photodetectors, and lasers. However, due to factors such as surface defects, solvent effects, light or oxidative environment, and structural defects, quantum dots are prone to surface structural damage or crystal structure distortion, which will affect their stability and performance in applications.
[0003] In order to promote the commercialization of quantum dots and their further application innovation and performance improvement in the fields of lighting, display, detection, etc., some studies have started from ligands, crystal structure, surface defect passivation, optimized synthesis methods, etc., to adjust the stability and optical properties of quantum dots, and even give rise to the development of new functions.
[0004] At present, the mainstream methods for preparing quantum dot films include: self-assembly method, solution evaporation method, nano-printing method, etc. These methods have problems such as high cost, uneven thickness, unstable film quality, and complex process, and are not suitable for large-scale industrial production and large-area film preparation. Therefore, it is urgent to design a method for preparing large-area quantum dot films with simple process, cost saving, flat film surface, uniform thickness, low defect state density, and high performance. Summary of the invention
[0005] The present invention aims at the deficiencies in the prior art and provides a method for preparing a large-area, high-performance quantum dot film.
[0006] The preparation method comprises the following steps:
[0007] S1, dissolving quantum dot precursor components and organic phosphoric acid in an organic solvent to prepare a precursor solution;
[0008] S2, adding a polymer to the precursor solution and mixing them evenly to obtain a membrane solution;
[0009] S3, coating the film solution on a substrate material, and then annealing to obtain a quantum dot film;
[0010] The quantum dot film comprises quantum dots modified by organic phosphoric acid and polymer.
[0011] Preferably, the quantum dots include at least one of group III-V quantum dots, group IV quantum dots, group II-VI quantum dots and perovskite quantum dots.
[0012] Preferably, the II-VI group quantum dots are quantum dots including zinc, cadmium and sulfur, selenium, and tellurium elements; the structural formula of the perovskite quantum dots is ABX3, wherein A is at least one element or group selected from cesium, rubidium, amine, and amidine, B is at least one selected from lead, tin, copper, zinc, germanium, arsenic, and manganese, and X is at least one selected from chlorine, bromine, and iodine.
[0013] Preferably, the organic linking group of the organophosphoric acid includes at least one of hydrocarbons, aromatics, alcohols, ethers, ketones, aldehydes, acids, esters, amines, and halogenated hydrocarbons.
[0014] Preferably, the organic solvent is an organic solvent that can dissolve the precursor components, including at least one of amide solvents, sulfone solvents, sulfoxide solvents, ester solvents, hydrocarbons, halogenated hydrocarbon solvents, alcohol solvents, ketone solvents, ether solvents, and aromatic hydrocarbon solvents.
[0015] Preferably, in the step S1, the molar ratio of each of the precursor components to the organic phosphoric acid is 1:
[0016] (0.2-0.5).
[0017] Preferably, in the step S2, the polymer is at least one of polymethyl methacrylate (PMMA), polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), polyvinyl chloride (PVC), polyvinylidene fluoride (PVDC), polystyrene (PS), and polycarbonate (PC); and the mass ratio of the polymer to the organic solvent is 1:(5-40).
[0018] Preferably, in the step S3, the annealing method is an annealing method selected from infrared radiation annealing and high temperature vacuum annealing; more preferably, the annealing method is high temperature vacuum annealing, the temperature of the high temperature vacuum annealing is 50-120°C, the annealing time is 10-120min, and the vacuum treatment pressure is not less than 10 -3 standard atmospheric pressure.
[0019] Preferably, in the step S3, the coating method is spin coating, blade coating, slit continuous coating, dip coating or spray coating;
[0020] More preferably, the coating method is a scraping method, the scraping speed is 3.0-20.0 mm / s, and the scraper height is 50-150 μm.
[0021] The present invention also relates to the use of a quantum dot film obtained according to the method for preparing the quantum dot film of the present invention in a lighting device, a display device, a photoelectric detector or a laser.
[0022] Compared with the existing method for preparing quantum dot thin films, the present invention has the following excellent effects:
[0023] (1) The preparation method of the present invention is suitable for preparing quantum dot films over a large area, and the method is simple and low in cost. The final film obtained has low roughness, low defect density, uniform thickness, and bright and uniform luminescence.
[0024] (2) The present invention introduces a new type of ligand into the precursor solution for preparing the film to modify the quantum dot structure: organic phosphoric acid, which can significantly improve the stability and optical properties of the quantum dots under heat, water and oxygen conditions. The present invention is particularly suitable for solving the optical stability and brightness problems of metal halide perovskite quantum dot films, because such quantum dots need to be excited by ultraviolet light and blue light, and the quantum dots are prone to defects such as ligand shedding and ion migration, resulting in reduced luminous efficiency. Therefore, adding a stabilizer polymer and coating it on the surface of the quantum dots with ligand coordination can improve the stability of the quantum dots.
[0025] (3) The organic phosphoric acid is more preferably benzyl phosphoric acid (BPA), because BPA has a shorter organic linking group, and can effectively enter the interior of the quantum dot crystal during the formation of the quantum dot film, effectively coordinate with the surface sites and reduce the defect density, forming a stable quantum dot structure. More preferably, the molar ratio of each of the precursor components and BPA is 1: (0.2-0.5), too low BPA will lead to weak coordination, still high surface defect density, and no obvious improvement in optical properties, while too high a content of BPA will lead to strong acidic conditions, which will affect the crystallization quality of the quantum dot film and ultimately produce a decrease in photoluminescence intensity.
[0026] (4) In addition, in the preparation method of the present invention, by improving the steps, that is, first adding the precursor components and the ligands to be dispersed in the solvent to form a precursor solution in which the ligands are uniformly dispersed, and then adding the polymer and mixing to form a uniform film solution, the uniformly dispersed film solution can achieve the final preparation of the surface of the quantum dots. The surface of the uniformly dispersed polymer and ligand can form a quantum dot film layer with uniform optical properties and thickness.
[0027] (5) The present invention adopts a uniform coating method, such as spin coating, blade coating, slit continuous coating, dip coating, spray coating, etc., to prepare a large-area high-performance quantum dot film with low roughness, low defect density, uniform thickness, and bright and uniform luminescence. Further, the blade coating method can be selected to prepare the quantum dot film. The blade coating method is simple and efficient to operate, has low equipment requirements, can more efficiently utilize raw materials, and reduce costs to the greatest extent.
[0028] (6) The preparation method of the present invention is easy to prepare large-area high-performance quantum dot films, and has industrial application prospects in the fields of display, lighting, lasers, photodetectors, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a schematic flow chart of a method for preparing a large-area, high-performance quantum dot film according to an embodiment of the present invention;
[0030] Figure 2 is the structural formula of BPA;
[0031] Figure 3 It is a schematic diagram of the structure of the scraping equipment in the embodiment of the present invention and the comparative example;
[0032] Figure 4 XRD diagrams of the quantum dot films of Example 1 and Comparative Example 1 of the present invention;
[0033] Figure 5 The actual image (a) of the CsPbBr3+BPA@PMMA large-area perovskite quantum dot film of Example 1 of the present invention and the corresponding thickness test data image of different areas (b);
[0034] Figure 6 is Rb of Example 2 of the present invention 0.5 Cs 0.5 Physical picture of PbI3+BPA@PMMA large-area perovskite quantum dot film (a) and corresponding thickness test data of different areas (b);
[0035] Figure 7 The actual image (a) of the CsPbBr3+BPA@PMMA large-area perovskite quantum dot film in Example 1 of the present invention and its luminescence image under 365nm ultraviolet light excitation (b);
[0036] Figure 8 is Rb in Example 2 of the present invention 0.5 Cs 0.5 Actual image of PbI3+BPA@PMMA large-area perovskite quantum dot film (a) and its luminescence image under 365nm ultraviolet light excitation (b);
[0037] Fig. 9 The photoluminescence intensity test (PL) result diagram of the quantum dot thin film of Examples 1 and 3 of the present invention and Comparative Example 1 (control group);
[0038] Fig.10 The environmental stability test results of quantum dot films of Example 1 of the present invention and Comparative Example 1 (control group) under different test conditions are shown;
[0039] Fig.11 This is a schematic diagram of the structure of the quantum dot film prepared in Examples 1 and 2 of the present invention used in a backlight module of a liquid crystal display;
[0040] Fig.12 The quantum dot films prepared in Examples 1 and 2 of the present invention are used in display effects of a backlight module of a liquid crystal display. DETAILED DESCRIPTION
[0041] The present invention provides a method for preparing a large-area, high-performance quantum dot film, which will be further described below with the aid of drawings and examples.
[0042] The preparation method comprises the following steps:
[0043] S1, dissolving quantum dot precursor components and organic phosphoric acid in an organic solvent to prepare a precursor solution;
[0044] S2, adding a polymer to the precursor solution and mixing them evenly to obtain a membrane solution;
[0045] S3, coating the film solution on a substrate material, and then annealing to obtain a quantum dot film;
[0046] The quantum dot film comprises: quantum dots modified by organic phosphoric acid and polymer.
[0047] Optionally, in step S1, the quantum dots include: at least one of group III-V quantum dots, group IV quantum dots, group II-VI quantum dots or perovskite quantum dots. Among them, group II-VI quantum dots are quantum dots including elements of group II (such as zinc, cadmium) and group VI (such as sulfur, selenium, tellurium); group III-V quantum dots are quantum dots including elements of group III (such as gallium, indium) and group V (such as arsenic, phosphorus); the perovskite quantum dots are halide perovskite quantum dots with a structural formula of ABX3, wherein A is at least any one of cesium, rubidium, amine, and amidine, B is any one of lead, tin, copper, zinc, germanium, arsenic, and manganese, and X is at least any one of chlorine, bromine, and iodine. More preferably, the quantum dots are metal halide perovskite quantum dots, and the precursor component is a metal halide corresponding to the preparation of quantum dots.
[0048] Optionally, in step S1, the organophosphoric acid is a ligand capable of being coordinated to a coordination group on the surface of the quantum dot, and the chemical structure of the organophosphoric acid includes a phosphate group and an organic linking group, wherein the organic linking group includes: hydrocarbons, aromatics, alcohols, ethers, ketones, aldehydes, acids, esters, amines, halogenated hydrocarbons and other organic linking groups; more preferably, the organophosphoric acid is benzylphosphoric acid (BPA). BPA can form in-situ coordination by simply reacting with a polycrystalline perovskite film; in addition, the BPA organic linking group is relatively short, and during the formation of the quantum dot film, it is easy to enter the interior of the quantum dot crystal, combine with the surface site, and form a quantum dot coated with a smaller size crystal, and passivate the uncoordinated metal atoms by forming a covalent bond, thereby greatly reducing the defect density of the quantum dot, while maintaining the good charge transfer performance of the perovskite. Finally, efficient, bright and stable optical properties are achieved.
[0049] Optionally, in step S1, the organic solvent is a solvent that can dissolve the quantum dot precursor components and is easily volatile, such as any one of amide solvents, sulfone solvents, sulfoxide solvents, ester solvents, hydrocarbons, halogenated hydrocarbon solvents, alcohol solvents, ketone solvents, ether solvents, and aromatic hydrocarbon solvents. For example: at least one of N,N-dimethylformamide and dimethyl sulfoxide, and more preferably a combination of two.
[0050] (7) Optionally, in step S1, the molar ratio of each of the precursor components to the organic phosphoric acid is 1:(0.05-0.5), for example, the molar ratio of each of the precursor components to the organic phosphoric acid can be 1:0.05, 1:0.1, 1:0.2, 1:0.3, 1:0.4, 1:0.5. In the precursor solution, the concentration of each precursor component is 0.05-2 mol / L. More preferably, the molar ratio of each of the precursor components to the organic phosphoric acid is 1:(0.2-0.5). Too low a content of BPA will result in weak coordination, still high surface defect density, and no obvious improvement in optical properties, while too high a content of BPA will result in strong acidic conditions, which will affect the crystallization quality of the quantum dot film and ultimately produce a decrease in photoluminescence intensity.
[0051] Optionally, in step S2, the polymer is at least one of polymethyl methacrylate (PMMA), polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), polyvinyl chloride (PVC), polyvinylidene fluoride (PVDC), polystyrene (PS), and polycarbonate (PC). The mass ratio of the polymer to the organic solvent is 1: (5-40), for example, the mass ratio of the polymer to the organic solvent can be 1: 5, 1: 10, 1: 20, 1: 30, or 1: 40. The mass ratio of the polymer to the organic solvent will affect the viscosity of the film solution, the scraping speed, annealing temperature and time during subsequent scraping and annealing film formation, and the coverage and flatness of the final film. For example, a too high mass ratio will cause the viscosity of the film solution to be too high, the subsequent scraping process will be relatively slow, and the flatness of the formed film will be low. A too low mass ratio will cause the annealing time of the film solution to be long, resulting in poor quality of the film layer.
[0052] Optionally, in step S3, the substrate is not particularly limited, and can be selected from the fields of lighting devices, new displays, photodetectors, lasers, etc. as transparent base materials commonly used to carry quantum dot films, such as quartz glass, sapphire, zinc oxide (ZnO), tin oxide (SnO2), polyethylene (PE), polyester (such as polybutylene terephthalate (PET), polybutylene terephthalate (PBT) or polyarylate (PAR)), polyimide (PI), polyethylene naphthalate (PEN), polydimethylsiloxane (PDMS), etc. The area of the substrate can be 200 to 400 cm 2 , for example 210cm 2 、220cm 2 、230cm 2 、240cm 2 、250cm 2 、270cm 2 、280cm 2 、290cm 2 、300cm 2 、310cm 2 、320cm 2 、330cm 2 、340cm 2 or 350cm 2 .
[0053] Optionally, in step S3, the temperature of the high temperature vacuum annealing is 50-120°C, the annealing time is 10-120 minutes, and the vacuum treatment pressure is not less than 10 -3standard atmosphere; preferably, the annealing temperature can be 110°C, 105°C, 100°C, 95°C, 90°C, 85°C, about 80°C, about 75°C, 70°C, 65°C or 60°C; the annealing time can be 120min, 100min, 80min, 60min, 40min, 20min or 10min; the pressure of the vacuum treatment can be 0.75 standard atmosphere, 0.5 standard atmosphere, 0.25 standard atmosphere, 0.1 standard atmosphere, 10 -2 standard atmosphere or 10 -3 standard atmospheric pressure.
[0054] Optionally, in step S3, the coating method is spin coating, scraper coating, slit continuous coating, dip pulling or spraying; more preferably, the coating method is scraper coating, and the scraper speed in the scraper coating method can be 3.0mm / s, 4.5mm / s, 6.0mm / s, 7.5mm / s, 9.0mm / s, 10.5mm / s, 12.0mm / s, 13.5mm / s, 15.0mm / s, 16.5mm / s or 18mm / s; the scraper height, that is, the distance between the scraper and the substrate material is 50μm, 60μm, 70μm, 80μm, 90μm, 100μm, 110μm, 120μm, 130μm, 140μm or 150μm.
[0055] The present invention will be described in detail below through a number of embodiments and comparative examples.
[0056] Example 1
[0057] Reference Figure 1 The process diagram of the preparation of CsPbBr3+BPA@PMMA large-area perovskite quantum dot film is as follows:
[0058] CsBr (0.1 mmol), PbBr2 (0.1 mmol), benzylphosphonic acid (BPA) (0.01 mmol, the molar ratio of each precursor component to BPA is 1:0.1), N, N-dimethylformamide (5 mL) were mixed and stirred to form a clear and transparent precursor solution, and then 400 mg PMMA was added to the above solution and stirred overnight at room temperature until it was completely clear and transparent to obtain a membrane solution. Among them, BPA is composed of a phosphate group and a benzyl group, i.e., a benzyl group, and its structural formula is as follows: Figure 2 As shown, the structure described in general formula I is satisfied.
[0059] Device reference Figure 3, place and adsorb a 15cm*15cm quartz glass substrate on an ultra-flat workbench to prevent the substrate from shifting during the scraping process, align the scraper above the edge of the substrate, and adjust the scraper to a suitable height, absorb an appropriate amount of film solution and drop it between the blade and the substrate. Due to the capillary effect, the film solution is evenly adsorbed between the blade and the substrate, start the push rod to push the scraper at a uniform speed of 6mm / s, remove the substrate after the scraping is completed, and anneal for 20min at a temperature of 80℃ under the condition of 0.15 standard atmospheric pressure. The film gradually changes from transparent to yellow, and a large-area CsPbBr3+BPA@PMMA perovskite quantum dot film is obtained.
[0060] Example 2
[0061] Reference Figure 1 Schematic diagram of the process, Rb 0.5 Cs 0.5 The preparation steps of PbI3+BPA@PMMA large-area perovskite quantum dot film are as follows:
[0062] CsI (0.05 mmol), RbI (0.05 mmol), PbI2 (0.1 mmol), BPA (0.01 mmol), and DMF (5 mL) were mixed and stirred thoroughly to form a clear and transparent precursor solution. Then 400 mg of PMMA was added to the above solution and stirred at room temperature until it was completely clear and transparent to obtain a membrane solution.
[0063] Device reference Figure 3 , place and adsorb a 15cm*15cm quartz glass substrate on an ultra-flat workbench to prevent the substrate from shifting during the scraping process, align the scraper above the edge of the substrate, and adjust the scraper to a suitable height, absorb a proper amount of film solution and drop it between the blade and the substrate. Due to the capillary effect, the film solution is evenly adsorbed between the blade and the substrate, start the push rod to push the scraper at a uniform speed of 4mm / s, remove the substrate after the scraping is completed, and anneal for 20min at a temperature of 90℃ under the condition of 0.15 standard atmospheric pressure. The film gradually changes from transparent to yellow, and Rb is obtained. 0.5 Cs 0.5 PbI3+BPA@PMMA large-area perovskite quantum dot film.
[0064] Example 3
[0065] Reference Figure 1 The process diagram of the preparation of CsPbBr3+BPA@PMMA large-area perovskite quantum dot films with different ratios is as follows:
[0066] CsBr (0.1 mmol), PbBr2 (0.1 mmol), BPA (0.02 mmol, 0.03 mmol, 0.04 mmol and 0.05 mmol, respectively, the molar ratio of each precursor component to BPA is 1:0.2, 1:0.3, 1:0.4, 1:0.5) was mixed with solvent DMF (5 mL), and stirred thoroughly to form a clear and transparent precursor solution. Then 400 mg PMMA was added to the above solution and stirred at room temperature until it was completely clear and transparent to obtain four membrane solutions with different BPA contents.
[0067] Device reference Figure 3 , place and adsorb a 15cm*15cm quartz glass substrate on an ultra-flat workbench to prevent the substrate from shifting during the scraping process, align the scraper above the edge of the substrate, and adjust the scraper to a suitable height, respectively absorb an appropriate amount of four membrane solutions and drop them between the blade and the substrate. Due to the capillary effect, the membrane solution is evenly adsorbed between the blade and the substrate, start the push rod to push the scraper at a uniform speed of 6mm / s, remove the substrate after the scraping is completed, and anneal for 20min at a temperature of 80℃ under the condition of 0.15 standard atmospheric pressure. The film gradually changes from transparent to yellow, and CsPbBr3+BPA@PMMA large-area perovskite quantum dot films with different BPA modification amounts are obtained.
[0068] Comparative Example 1
[0069] Reference Figure 1 The process diagram of the preparation of CsPbBr3@PMMA large-area perovskite quantum dot film is as follows:
[0070] CsBr (0.1 mmol), PbBr2 (0.1 mmol), and N,N-dimethylformamide (DMF) (5 mL) were mixed and stirred thoroughly to form a clear and transparent precursor solution. Then, 400 mg of PMMA was added to the above solution and stirred at room temperature until it was completely clear and transparent to obtain a membrane solution.
[0071] Device reference Figure 3 , place and adsorb a 15cm*15cm quartz glass substrate on an ultra-flat workbench to prevent the substrate from shifting during the scraping process, align the scraper above the edge of the substrate, and adjust the scraper to a suitable height, absorb an appropriate amount of film solution and drop it between the blade and the substrate. Due to the capillary effect, the film solution is evenly adsorbed between the blade and the substrate. Start the push rod to push the scraper at a uniform speed of 6mm / s. After the scraping is completed, remove the substrate, and anneal for 20min at a temperature of 80℃ under vacuum conditions of 0.15 standard atmospheric pressure. The film gradually changes from transparent to green, and a large-area CsPbBr3@PMMA perovskite quantum dot film is obtained.
[0072] Comparative Example 2
[0073] Reference Figure 1 Schematic diagram of the process, Rb 0.5 Cs 0.5 The preparation steps of PbI3@PMMA large-area perovskite quantum dot film are as follows:
[0074] CsI (0.05 mmol), RbI (0.05 mmol), PbI2 (0.1 mmol), and DMF (5 mL) were mixed and stirred thoroughly to form a clear and transparent precursor solution. Then, 400 mg of PMMA was added to the above solution and stirred at room temperature until it was completely clear and transparent to obtain a membrane solution.
[0075] Device reference Figure 3 , place and adsorb a 15cm*15cm quartz glass substrate on an ultra-flat workbench to prevent the substrate from shifting during the scraping process, align the scraper above the edge of the substrate, and adjust the scraper to a suitable height, absorb a proper amount of film solution and drop it between the blade and the substrate. Due to the capillary effect, the film solution is evenly adsorbed between the blade and the substrate, start the push rod to push the scraper at a uniform speed of 4mm / s, remove the substrate after the scraping is completed, and anneal for 20min at a temperature of 90℃ under the condition of 0.15 standard atmospheric pressure. The film gradually changes from transparent to red, and Rb is obtained. 0.5 Cs 0.5 PbI3@PMMA large-area perovskite quantum dot film.
[0076] Characterization Tests:
[0077] Figure 4 The XRD results are the test results of the quantum dot films of Example 1 and Comparative Example 1, indicating that the addition of BPA as a ligand maintains the crystal form of the quantum dots and has no effect on the crystal structure of the quantum dots.
[0078] Figure 5 , Figure 6 The thickness test results of the quantum dot films of Example 1 and Example 2 are respectively tested by the step meter. The thickness of each quantum dot film is tested at 9 different positions. It can be seen that in the thickness test data of green light, the thickness of 6 test positions is between 3.30 and 3.41 μm, and the thickness of 9 test positions of the quantum dot film of red light is between 3.16 and 3.25 μm, indicating that the present invention achieves a high uniformity in the thickness of the quantum dot film by introducing BPA and polymer combined with scraping technology.
[0079] Reference Figure 7 , which are the actual picture of the quantum dot film obtained in Example 1 (a) and its luminescence picture under 365nm ultraviolet light excitation (b). It can be seen that the quantum dot film emits green light under 365nm ultraviolet light excitation.
[0080] Reference Figure 8 , which is a physical picture of the quantum dot film of Example 2 (a) and its luminescence picture under 365nm ultraviolet light excitation (b). It can be seen that the quantum dot film emits red light under 365nm ultraviolet light excitation.
[0081] Reference Fig. 9 , are the PL spectrum test results of quantum dot films with different BPA contents obtained in Example 1, Example 3 and Comparative Example 1 (control group). By comparison, it can be seen that the surface defects can be effectively passivated by modification of the BPA ligand, which is manifested in enhanced photoluminescence intensity, and when the molar ratio of each of the precursor components and BPA is adjusted from 1:0.1 to 1:0.2, the photoluminescence intensity is significantly improved, and as the molar ratio of the two is gradually adjusted to 1:0.5, the photoluminescence intensity decreases. This is because too much BPA may produce strong acidic conditions, which will affect the crystallization quality of the quantum dot film and ultimately lead to a decrease in photoluminescence intensity.
[0082] refer to Fig.10 , the PL spectrum test results of the quantum dot film prepared by the process described in Example 1 (after BPA modification) and Comparative Example 1 (control group) during 1000h accelerated aging are respectively shown, and the aging experimental conditions are (a) room temperature, 365nm ultraviolet light irradiation; (b) 50℃ high temperature, relative humidity RH~70%. It can be seen from the results that the ultraviolet light stability and wet-heat stability of the CsPbBr3+BPA@PMMA quantum dot film described in Example 1 are significantly improved compared with those of the CsPbBr3@PMMA quantum dot film described in Comparative Example 1, thereby achieving the purpose of improving the stability of the perovskite quantum dot film.
[0083] refer to Fig.11 The perovskite quantum dot film prepared by the method of the present invention is made into a liquid crystal display backlight module. According to Example 1 and Example 2, 15 cm×15 cm green (CsPbBr3+BPA@PMMA) and red (Rb0.5Cs0.5PbI3+BPA@PMMA) color conversion films are prepared and excited with a blue LED light source to achieve the display purpose. The display effect is as follows. Fig.12 As shown, it can be seen that the backlight module prepared by the quantum dot film prepared in Example 1 and Example 2 of the present invention has a very clear, realistic and colorful display effect, and can be applied to the backlight source device of the wide color gamut liquid crystal display.
[0084] The above embodiments are only used to further illustrate the preparation method and application of a large-area high-performance perovskite film of the present invention, and are not limitations on the implementation methods and implementation objects. The present invention is not limited to the embodiments, and other different forms of changes can be made on the basis of the above description. It is not necessary and impossible to list all the implementation methods here, and the obvious changes derived therefrom also fall within the scope of protection of the present invention.
Claims
1. A method for preparing a quantum dot film, characterized in that: The following steps are involved: S1, dissolving quantum dot precursor components and organic phosphoric acid in an organic solvent to prepare a precursor solution; S2, adding a polymer to the precursor solution and mixing them evenly to obtain a membrane solution; S3, coating the film solution on a substrate material, and then annealing to obtain a quantum dot film; The quantum dot film comprises quantum dots modified by organic phosphoric acid and polymer.
2. The method for preparing a quantum dot thin film according to claim 1, characterized in that: The quantum dots include at least one of group III-V quantum dots, group IV quantum dots, group II-VI quantum dots and perovskite quantum dots.
3. The method for preparing a quantum dot thin film according to claim 2, characterized in that: The structural formula of the perovskite quantum dot is ABX3, wherein A is cesium, rubidium or an amine or amidine group, B is at least one of lead, tin, copper, zinc, germanium, arsenic and manganese, and X is at least one of chlorine, bromine and iodine.
4. The method for preparing a quantum dot thin film according to claim 1, characterized in that: The organic linking group of the organic phosphoric acid includes at least one of hydrocarbons, aromatics, alcohols, ethers, ketones, aldehydes, acids, esters, amines, and halogenated hydrocarbons.
5. The method for preparing a quantum dot thin film according to claim 2, characterized in that: The organic solvent is an organic solvent that can dissolve the precursor components, including at least one of amide solvents, sulfone solvents, sulfoxide solvents, ester solvents, hydrocarbons, halogenated hydrocarbon solvents, alcohol solvents, ketone solvents, ether solvents, and aromatic hydrocarbon solvents; more preferably, the organic solvent is at least one of N,N-dimethylformamide and dimethyl sulfoxide.
6. The method for preparing a quantum dot thin film according to claim 1, characterized in that: In the step S1, the molar ratio of each of the precursor components to the organic phosphoric acid is 1:(0.2-0.5).
7. The method for preparing a quantum dot thin film according to claim 1, characterized in that: In the S2 step, the polymer is at least one of polymethyl methacrylate (PMMA), polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), polyvinyl chloride (PVC), polyvinylidene fluoride (PVDC), polystyrene (PS), and polycarbonate (PC); and the mass ratio of the polymer to the organic solvent is 1:(5-40).
8. The method for preparing a quantum dot thin film according to claim 1, characterized in that: In the step S3, the annealing method is an annealing method selected from infrared radiation annealing and high temperature vacuum annealing; more preferably, the annealing method is high temperature vacuum annealing, the temperature of the high temperature vacuum annealing is 50-120°C, the annealing time is 10-120min, and the vacuum treatment pressure is not less than 10 -3 standard atmospheric pressure.
9. The method for preparing a quantum dot thin film according to claim 1, characterized in that: In the step S3, the coating method is spin coating, blade coating, slit continuous coating, dip coating or spray coating; More preferably, the coating method is a scraping method, the scraping speed is 3.0-20.0 mm / s, and the scraper height is 50-150 μm.
10. Application of the quantum dot film obtained by the method for preparing the quantum dot film according to any one of claims 1 to 9 in lighting devices, display devices, photodetectors, and lasers.